1999
DOI: 10.1038/sj.bjc.6690147
|View full text |Cite
|
Sign up to set email alerts
|

p53 mutations in human cutaneous melanoma correlate with sun exposure but are not always involved in melanomagenesis

Abstract: SummaryIn melanoma, the relationship between sun exposure and the origin of mutations in either the N-ras oncogene or the p53 tumoursuppressor gene is not as clear as in other types of skin cancer. We have previously shown that mutations in the N-ras gene occur more frequently in melanomas originating from sun-exposed body sites, indicating that these mutations are UV induced. To investigate whether sun exposure also affects p53 in melanoma, we analysed 81 melanoma specimens for mutations in the p53 gene. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
51
0
8

Year Published

2000
2000
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 82 publications
(63 citation statements)
references
References 22 publications
(33 reference statements)
4
51
0
8
Order By: Relevance
“…Interestingly, the tumour suppressor gene for TP53 is mutated in a high proportion of cancers, but very few melanomas 70 . The inactivation of p53 through the deletion or mutation of TP53 leads to a reduced level of apoptotic cell death, providing the cell with increased survival potential.…”
Section: Chemoresistance and Treatment In Malignant Melanomamentioning
confidence: 99%
“…Interestingly, the tumour suppressor gene for TP53 is mutated in a high proportion of cancers, but very few melanomas 70 . The inactivation of p53 through the deletion or mutation of TP53 leads to a reduced level of apoptotic cell death, providing the cell with increased survival potential.…”
Section: Chemoresistance and Treatment In Malignant Melanomamentioning
confidence: 99%
“…Interestingly, a recent report has shown that a small percent of wild type p53 localizes to the mitochondria in several types of human cancer cell lines that have been induced into apoptosis by chemotherapy agents and growth factor withdrawal (Marchenko et al, 2000). The frequency of p53 mutations in human melanomas are lower than in most other cancer types (10 ± 30% vs 50%, respectively) (Albino et al, 1994;Zerp et al, 1999) and the role of p53 in the induction of apoptosis in melanoma is still incompletely understood.…”
Section: Introductionmentioning
confidence: 99%
“…Arginine at codon 209 was found mutated in 69 tumors, including five tumors that harbor the exact arginine-to-lysine replacement. [35][36][37][38][39] Multiple alignment performed among 44 species indicated that the amino acid at position 209 in humans is not a Spalax-unique change. Actually, there is a vast variability at this nonconserved region, with 10 different amino acid possibilities among the species examined.…”
Section: Spalax P53 Biologymentioning
confidence: 99%